2017
DOI: 10.18052/www.scipress.com/ilns.63.27
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Quality of Table Eggs Using Vegetable Oil and Shea Butter

Abstract: Abstract. The poultry industry in Nigeria keeps expanding on a daily basis and it is faced with the problem of egg glut almost yearly. Most of the poultry are raised in rural environments where there is no available and avoidable power supply for egg preservation. The study was aimed at using locally available and cheap materials for preservation of eggs quality under the hot ambient temperature. The eggs were divided into three groups of 80 eggs each. The first and second groups were treated with vegetable oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…The significant differences observed could be explained that the use of vegetable oil was effective in preventing deterioration, maintaining interior quality, the albumen weight and yolk weight as compared to the other treatment groups. This result is in agreement with Okiki and Ahmed [17] who reported that coating eggs with vegetable oil prevents loss of moisture and carbon dioxide via the shell pores thereby maintaining interior quality of chicken eggs.…”
Section: Effect Of Storage Methods On Egg Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…The significant differences observed could be explained that the use of vegetable oil was effective in preventing deterioration, maintaining interior quality, the albumen weight and yolk weight as compared to the other treatment groups. This result is in agreement with Okiki and Ahmed [17] who reported that coating eggs with vegetable oil prevents loss of moisture and carbon dioxide via the shell pores thereby maintaining interior quality of chicken eggs.…”
Section: Effect Of Storage Methods On Egg Characteristicssupporting
confidence: 92%
“…This can be further explained that, the efficacy of oils in preservation of eggs has been attributed to the ability of oil in blocking the air pores of the egg shells, thereby preventing the flow of air in and out of the eggs and degradation by the contaminants such as air may carry [16]. Similar findings were reported by Okiki and Ahmed [17]. The significant differences observed could be attributed to the level of vegetable used in this experiment.…”
Section: Effect Of Storage Methods On Egg Weight and Embryonic Developmentsupporting
confidence: 82%